The influence of match status on the conditional characteristics of tactical sprint actions in professional soccer players - Lobo-Triviño, D.; García-Calvo, T.; Rubio-Morales, A.; Nevado, F.; Chena, M.; Piñero-Madrona, J. A.; Martín-Ardila, E.; Raya-González, J. (Biology of Sport, 2024)
This study aimed to analyse the influence of the match status on the conditional characteristics of tactical sprint actions among Spanish professional soccer players, considering playing positions. Thirty-two Spanish male professional soccer players from a LaLiga Spanish Second Division (LaLiga SmarthBank) team participated in this study. Actions above 85% of the players` maximum velocity were analysed based on their tactical purpose. These findings provide valuable information regarding the tactical aspects of sprinting in soccer, emphasizing the influence of playing positions and match status on the distribution of tactical sprint actions. No effects of match status were observed for any game phase. However, when tactical actions were individually studied, it was observed that the maximum velocity in Chase actions was higher when the team was winning, while in Press actions, the maximum velocity was higher when the team was losing and in in Run in behind/Penetrate, the maximum velocity was higher in drawing situations compared to losing situations. No effects of match status on the distance covered during sprinting were observed, and regarding duration, significant differences were only observed in Recovery run actions. In addition, the influence of match status is higher when playing positions are considered, although the within playing positions analysis revealed significant differences only in CM players. These findings provide valuable information for the design of specific training drills considering playing positions, suggesting the need to analyse the previous match in order to structure the training load of the microcycle in a comprehensive manner.